The Kingdom of Swaziland : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report, 2006)
Economic growth in Swaziland has weakened over the past decade. This 2005 Article IV Consultation highlights that real GDP growth decelerated to 2.1 percent in 2004 and an estimated 1.8 percent in 2005. A prolonged drought affected agricultural output, particularly maize, the main staple crop, and cotton. The authorities completed a 'Poverty Reduction Strategy and Action Plan' in October 2004. The document spells out policies with the overall objective of halving the 1995 poverty rate by 2015. However, little progress has been made toward this and other Millennium Development Goals.